38+6x=-4(7-7x)

Simple and best practice solution for 38+6x=-4(7-7x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 38+6x=-4(7-7x) equation:


Simplifying
38 + 6x = -4(7 + -7x)
38 + 6x = (7 * -4 + -7x * -4)
38 + 6x = (-28 + 28x)

Solving
38 + 6x = -28 + 28x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-28x' to each side of the equation.
38 + 6x + -28x = -28 + 28x + -28x

Combine like terms: 6x + -28x = -22x
38 + -22x = -28 + 28x + -28x

Combine like terms: 28x + -28x = 0
38 + -22x = -28 + 0
38 + -22x = -28

Add '-38' to each side of the equation.
38 + -38 + -22x = -28 + -38

Combine like terms: 38 + -38 = 0
0 + -22x = -28 + -38
-22x = -28 + -38

Combine like terms: -28 + -38 = -66
-22x = -66

Divide each side by '-22'.
x = 3

Simplifying
x = 3

See similar equations:

| 4x+3+28=4x+48 | | 36-5=4 | | -7=3n+3-1 | | expression | | 15-5x=4x+18 | | 5X-3-3X+7= | | 11m+3=4(m-8) | | 3(2x+2)+5(x-2)=-x+10 | | 9+2.7t=-4.8+(-6) | | 12-e=7 | | 1.75x+2.50y=195 | | 3x-6-5x+5=-7 | | 3x+y=-26 | | 3+2(4-x)=3x-7 | | 9(k)=36 | | -41=n-22 | | -8(a/8-2)=26 | | 2b-4=3(b+4) | | 12x-132=84 | | 50x^2-8=y | | 7x+18=x+10 | | x^3+4x^2-64x-256=x+24 | | 2x-3(3x-4)=4x-12 | | 21-v=16 | | 4+8=6(6) | | -77+7y=10x | | 4/5-4=3/1+12 | | 23x-5=-1.7x-5 | | -3(7n-6)=31-8n | | 3x-1=6x+20 | | u-15=1.5 | | 48=3k+12-k-4 |

Equations solver categories